2011
DOI: 10.1002/aenm.201100390
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Reduced Bimolecular Recombination in a Novel Silole‐Based Polymer: Fullerene Blend

Abstract: Charge transport measurements reveal non‐Langevin recombination for KP115:PCBM organic photovoltaic devices. This rare but highly advantageous behaviour allows a long charge carrier drift length and thus devices with thick active layers retain a high fill factor. However, no clear correlation with morphology was found, indicating that the origin of non‐Langevin recombination may be more complex than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 27 publications
(71 reference statements)
5
67
0
Order By: Relevance
“…Prior to light degradation, the calculated mobility is ~ 8 x 10 -4 cm 2 V -1 s -1 ; this value is higher than that previously published. [10] This could be because in this study the device area was reduced by a factor of three (to ~ 5 mm 2 ) in order to minimise RC limitations and better resolve t max . Furthermore, the devices measured here have much higher efficiencies (4.4 % rather than the previous 3.0 % [10] ).…”
Section: Photo-celivmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to light degradation, the calculated mobility is ~ 8 x 10 -4 cm 2 V -1 s -1 ; this value is higher than that previously published. [10] This could be because in this study the device area was reduced by a factor of three (to ~ 5 mm 2 ) in order to minimise RC limitations and better resolve t max . Furthermore, the devices measured here have much higher efficiencies (4.4 % rather than the previous 3.0 % [10] ).…”
Section: Photo-celivmentioning
confidence: 99%
“…. [9][10][11][12][13] This polymer, although it does not attain the high efficiencies of PCDTBT:PCBM in thin (< 100 nm) active layer thickness devices, has particularly interesting characteristics in thick (> 200 nm active layer) devices. KP115:PCBM devices, which can reach efficiencies of 5 %, possess the rare but highly desirable characteristic that the active layer can be considerably thicker without a detrimental effect on the efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Most importantly, in some blends, the recombination rate has been found to be several orders of magnitude less than what is predicted by the Langevin model. 8,[24][25][26][27][28][29][30][31][32][33] As a result, many of these studies have determined the Langevin reduction factor (ζ), where…”
mentioning
confidence: 99%
“…However, in other seemingly similar systems, recombination rates much closer to the Langevin model were observed. 14,26,27,[34][35][36] Even blends with very similar morphology can have dramatically different recombination rates.…”
mentioning
confidence: 99%
“…Assuming a reasonable built-in eld, it is found that the IQE for c b ¼ 0 drastically depends on the non-Langevin factor: 30 In summary, Fig. 6 shows that in the case of Si-PCPDTBT reduced mobility and enhanced background carrier concentration easily account for the observed loss of J SC upon photo-oxidation of the active layer (see Fig.…”
mentioning
confidence: 99%